Evaluation of Newcastle disease virus as an oncolytic agent in colorectal cancer cell lines - Chia, Suet Lin (2012)
Reports showing tumour regression in cancer patients following viral infections appeared at the beginning of the last century. By the 1950s, several viruses including Newcastle disease virus (NDV) showed positive oncolytic activities. Since then, NDV with its natural ability to infect cancer cells has been widely studied as a candidate in viral oncolysis. In the present study, oncolytic effect of a local NDV isolate, strain AF2240, was analysed in a panel of colorectal cancer (CRC) cell lines. Prior to infection studies, a modified plaque assay using CRC cells as hosts was established. SW620 was found to be the best cell line to be used for NDV plaque assay because of the size, clarity, and also the number of plaques formed. The plaque forming unit (pfu)/ mL of NDV was determined and subsequently used for the infection studies. All the CRC lines underwent apoptosis upon NDV infection. The presence of syncytia, a characteristic of paramyxoviral infection, proved that these cells were indeed infected by the virus. In addition, sandwich ELISA and plaque assays performed on spent culture supernatants showed that infectious viral progenies were released into the medium. The effects of NDV infection on the Ras/Akt/PKB pathway in these CRC cells with multiple gene mutations (in K-Ras, p53, and APC) were analysed. Comparison between these cell lines showed that all the cells experienced down-regulation of pAkt upon NDV infection. This down-regulation, however, did not affect its downstream effector, pGSK3β. Thus the β-catenin protein level was also not down-regulated in all the cells. It is not surprising, however, that the pGSK3β and β-catenin were down-regulated in the HCT116p53-/- cells as these cells possess wild type APC and the p53 gene is knocked out in both alleles. From these results, it is possible to suggest that it may not be effective to use therapeutic agents targeting the Ras/Akt/PKB pathway for CRC treatment. Regardless of the effect of NDV infection on the cell proliferation pathway, NDV did up-regulate BAD, down-regulate pBAD or reduce the Bax/Bcl-2 levels (depending on the cell lines) leading to apoptosis in these cells. The SW480 cells experienced a down-regulation of the pAkt during a primary infection (at 25 hpi or earlier) but recovered gradually during a secondary infection (after 25 hpi) when the pAkt level increased. Repeated exposures of NDV to these cells did not induce any cellular apoptosis. These cells were then labelled as SW480P as they were found to be persistently infected with the virus. Microscopic analysis of the SW480P, with or without re-infection of NDV, showed an identical physical appearance to that of the parental SW480 cells. RT-PCR and immunofluorescent analyses of one of the most abundant NDV protein, the nucleocapsid protein (NP) showed that the viral RNA and proteins were present in the uninfected SW480P. However, the newly synthesized viral progenies showed smaller plaques compared to wild type NDV suggesting that defective interfering particles (DIP) were produced. This abortive infection resulting in the production of DIPs may explain why some cancer cells resist the oncolytic effect by the virus during virotherapy. This study demonstrated the potential of NDV as an oncolytic agent in various CRC cell lines. NDV mediated the oncolysis through suppression of the Ras/Akt/PKB pathway leading to apoptosis. Cellular apoptosis occur in CRC cells, regardless of the genetic mutations acquired, by the reduction of the Bax/Bcl-2 ratio, up-regulation of BAD and down-regulation of pBAD. Despite the robust pro-apoptotic ability of NDV, a small percentage (17%) of cells in the infected population, survived the infection even after 97 hpi. Following rescue and further propagation, these cells were found to be persistently infected with NDV. Viral progenies were actively secreted into the culture media. However, these secreted viruses were found to be less infectious and showing reduced oncolytic activities, characteristic of DIPs. Results obtained from this study will contribute towards further understanding of the mechanisms of NDV-induced oncolysis. This information will be useful for improving NDV as a candidate for cancer virotherapy.